2016
DOI: 10.18632/oncotarget.8366
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor regulates SRC expression through microRNA-203

Abstract: The SRC kinase has pivotal roles in multiple developmental processes and in tumor progression. An inverse relationship has been observed between androgen receptor (AR) activity and SRC signaling in advanced prostate cancer (PCa); however, the modulation of AR/SRC crosstalk that leads to metastatic PCa is unclear. Here, we showed that patients with high SRC levels displayed correspondingly low canonical AR gene signatures. Our results demonstrated that activated AR induced miR-203 and reduced SRC levels in PCa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…Interestingly, AR‐regulated miRNAs are not always oncogenic. For example, AR‐regulated miR‐135a and miR‐203 inhibits PCa cell growth, migration and invasion through downregulating ROCK1/ROCK2 and SRC respectively . In the present study, we demonstrate miR‐193a‐3p is an AR target gene and promotes PCa cell migration through its direct target AJUBA.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, AR‐regulated miRNAs are not always oncogenic. For example, AR‐regulated miR‐135a and miR‐203 inhibits PCa cell growth, migration and invasion through downregulating ROCK1/ROCK2 and SRC respectively . In the present study, we demonstrate miR‐193a‐3p is an AR target gene and promotes PCa cell migration through its direct target AJUBA.…”
Section: Discussionsupporting
confidence: 56%
“…Studies confirmed that targeting SRC by means of a miR-203 mimic could be a hopeful curative approach for SRC signaling-activated PCa treatment (Siu et al, 2016).…”
Section: Mirnas and Resistance To Second-generation Ar Antagonists (Enzalutamide And Abiraterone)mentioning
confidence: 81%
“…A reduction in AR-induced miR-203 levels has been associated with an increased growth and migration potential of prostate cancer cells. The dysregulation of the AR signaling in prostate cancer cells results in the over-expression of SRC and enhancement of metastatic ability of these cells [104].…”
Section: Effects Of Circrnas On Armentioning
confidence: 99%